2003
DOI: 10.5424/sjar/2003014-42
|View full text |Cite
|
Sign up to set email alerts
|

Effect on pig performance of feed restriction during the growth period

Abstract: Two experiments were conducted to determine the compensatory responses of pig to feed restriction during the growth period. Eighty Dalland pigs (40 boars and 40 gilts) and 60 Large White × (Large White × Landrace) barrows were used in two different experiments. They were slaughtered at 97 and 122 kg. During the restriction period, the animals were restricted by 46% and 25% of their ad libitum consumptions in experiment 1 and 2 respectively. The restriction periods lasted 28 and 35 days respectively. Considerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0
7

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 10 publications
4
18
0
7
Order By: Relevance
“…These unexpected results, which were owing to reductions in ADG and G : F ratio in the RE piglets receiving PE compared with the piglets given water without PE supplementation, may indicate that this PE product cannot increase growth performance for piglets with a RE feeding regimen in the short post-weaning period. Similar results have been found by Daza et al (2003), who reported that pigs fed a RE diet reduced their feed intake but had a feed conversion ratio similar to that of pigs fed AD. Rantzer et al (1996) reported that, during the period of feeding restriction, the RE piglets had a lower diarrhoea score than those fed AD.…”
Section: Discussionsupporting
confidence: 89%
“…These unexpected results, which were owing to reductions in ADG and G : F ratio in the RE piglets receiving PE compared with the piglets given water without PE supplementation, may indicate that this PE product cannot increase growth performance for piglets with a RE feeding regimen in the short post-weaning period. Similar results have been found by Daza et al (2003), who reported that pigs fed a RE diet reduced their feed intake but had a feed conversion ratio similar to that of pigs fed AD. Rantzer et al (1996) reported that, during the period of feeding restriction, the RE piglets had a lower diarrhoea score than those fed AD.…”
Section: Discussionsupporting
confidence: 89%
“…As características nutricionais estabelecidas no trabalho e o padrão genético dos animais avaliados podem ter sido responsáveis por esse resultado, que não correspondeu à melhora da conversão. Esse resultado contraria os dados obtidos por Daza et al (2003), que verificaram os efeitos da restrição de 25% em relação ao consumo à vontade durante 35 dias, com início aos 32,8 kg PC, e notaram melhora de 9% na conversão alimentar aos 35 dias após a restrição.…”
Section: Resultsunclassified
“…In some experiments compensatory growth produced pigs with leaner carcass (Campbell et al, 1983;Donker et al, 1986). However, other studies observed no difference in carcass traits at slaughter between restricted pigs and pigs with ad libitum access to feed during growth period (Prince et al, 1983;Valaja et al, 1992;Critser et al, 1995;Daza et al, 2003). On other hand, the possible influence of compensatory growth on backfat fatty acid composition of selected pigs has been hardly studied, although fatty acid metabolism is largely affected by feed intake and metabolic regulation.…”
Section: Introductionmentioning
confidence: 94%
“…Thus, Wiesemüller et al (1978) observed an improvement of overall average daily gain as well as feed conversion ratio while Campbell et al (1983), Prince et al (1983) and Donker et al (1986) found an improvement only in overall feed conversion ratio and not in average daily gain when feeding level was restricted during grower phase. Critser et al (1995) and Daza et al (2003) found no improvement either in overall daily gain or in feed efficiency, despite the compensatory growth during the finishing period.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation